ASH LAYERS FROM SOUTH ANDAMAN SEA: PROBABLY SOURCED FROM TOBA CALDERA - Sachin Kumar Tripathi; Manoj R.V.; Mritunjay Chaturvedi; Resmi S (Marine Geological Institute of Indonesia, 2022)
Deep Sea sediment core PC-1 from the South Andaman Sea (7 ̊19.85' N; 94 ̊ 39.26' E; in East Andaman Basin) below the water depth of 3144 m contain discrete ash layers at various depths. According to morphological study, these ash layers contain glass shards of different varieties i.e. Type-I, Type-II, Type-III, Type-IV and Type-V and it is comparable to glass shards of Toba volcanic reported from other parts of the world. This observation is also supported on the basis of relative biostratigraphic datum observed in the core PC-1. The Layer-A (56 cm thick) at 210 cm bsf is just above the biostratigraphic datum of ca. 0.12 Ma, correspond to Youngest Toba Tuff (YTT), followed by Layer-C belongs to Middle Toba Tuff (MTT) and Layer-D inferred as Oldest Toba Tuff (OTT). This interpretation is further supported by the geochemical data obtained from the EDX analysis, which suggest high silica and alkali contents of rhyolitic composition. Hence, geochemical composition, morphology and biostratigraphic data of these discrete tephra layers show identical characteristics to the products of Toba eruptions, including YTT, MTT and OTT.